Supercapacitive microbial desalination cells: New class of power generating devices for reduction of salinity content. (15th December 2017) - Santoro, Carlo; Abad, Fernando Benito; Serov, Alexey; Kodali, Mounika; Howe, Kerry J.; Soavi, Francesca; Atanassov, Plamen
Graphical abstract: Supercapacitive Microbial Desalination Cell is here presented with unprecedented performances. Anode and cathode act as negative and positive electrode of an internal supercapacitor that is discharged and self-recharged. Maximum power of 3 W m −2 is recorded. Highlights: The concept of supercapacitive microbial desalination cell is here presented. The device is able to degrade organics, desalinate and generate power simultaneously. An additional electrode overcomes cathode ohmic losses and boost up power output. Maximum power achieved was 3.0 W m −2 (2.1 mW). 7600 discharge/self-recharge cycles were demonstrated over 44 h. Abstract: In this work, the electrodes of a microbial desalination cell (MDC) are investigated as the positive and negative electrodes of an internal supercapacitor. The resulting system has been named a supercapacitive microbial desalination cell (SC-MDC). The electrodes are self-polarized by the red-ox reactions and therefore the anode acts as a negative electrode and the cathode as a positive electrode of the internal supercapacitor. In order to overcome cathodic losses, an additional capacitive electrode (AdE) was added and short-circuited with the SC-MDC cathode (SC-MDC-AdE). A total of 7600 discharge/self-recharge cycles (equivalent to 44 h of operation) of SC-MDC-AdE with a desalination chamber filled with an aqueous solution of 30 g L −1 NaCl are reported. The same reactor system was operated with real seawater collected from Pacific Ocean for 88 h (15, 100 cycles). Maximum power generated was 1.63 ± 0.04 W m −2 for SC-MDC and 3.01 ± 0.01 W m −2 for SC-MDC-AdE. Solution conductivity in the desalination reactor decreased by ∼50% after 23 h and by more than 60% after 44 h. There was no observable change in the pH during cell operation. Power/current pulses were generated without an external power supply.